2010
DOI: 10.1901/jeab.2010.93-485
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Postdiscrimination Gradients Within a Stimulus Dimension Based on Bilateral Facial Symmetry

Abstract: A shift in generalization gradients away from S+ and towards stimuli on the opposite end of the stimulus dimension from S- is a well established phenomenon in the laboratory, occurring with humans and nonhumans and with a wide range of stimuli. The phenomenon of gradient shifts has also been observed to have an analogous relationship to a variety of apparent biases in preference observed in the natural environment. One way to examine the validity of such analogies is by examining whether gradient shifts can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…The average behavioral generalization gradient during the test phase is depicted in Figure 3A. In line with previous findings (Purtle, 1973;Wisniewski et al, 2009;Derenne, 2010), we found a strong peak shift, i.e., the peak of the generalization gradient was displaced from the CSϩ, in the direction away from the CSϪ (t test between responses left vs right of the CSϩ; t ϭ 3.28, p Ͻ 0.01). Moreover, response times (RTs) were modulated by the orientation of the stimulus (one-way ANOVA with repeated measures, F (14,308) ϭ 4.83, p Ͻ 0.001) and revealed a similar gradient as the behavioral responses (higher RT with higher probability of ϩ responses).…”
Section: Behavioral Generalization Gradientsupporting
confidence: 91%
See 1 more Smart Citation
“…The average behavioral generalization gradient during the test phase is depicted in Figure 3A. In line with previous findings (Purtle, 1973;Wisniewski et al, 2009;Derenne, 2010), we found a strong peak shift, i.e., the peak of the generalization gradient was displaced from the CSϩ, in the direction away from the CSϪ (t test between responses left vs right of the CSϩ; t ϭ 3.28, p Ͻ 0.01). Moreover, response times (RTs) were modulated by the orientation of the stimulus (one-way ANOVA with repeated measures, F (14,308) ϭ 4.83, p Ͻ 0.001) and revealed a similar gradient as the behavioral responses (higher RT with higher probability of ϩ responses).…”
Section: Behavioral Generalization Gradientsupporting
confidence: 91%
“…Although the test stimuli have never been paired with reward, animals respond to test stimuli that are similar to the CSϩ. A key finding in these experiments is the peak shift (Purtle, 1973;Wisniewski et al, 2009;Derenne, 2010): the peak of the generalization gradient is displaced from the CSϩ, in the direction away from the CSϪ, thereby enhancing the subjective difference between CSϩ and CSϪ.…”
Section: Introductionmentioning
confidence: 99%
“…The sheep individuals however differed in their actions, with four out of six rams clearly avoiding the ergot-containing forage, and two always trying to eat from the container they first approached. The variance in behaviour among individuals, which is common in choice experiments on learning behaviour (e.g., [47]), may be due to the individual characters and abilities, either in adjusting to short-term experimental settings or in the ability to detect and/or avoid ergot. With the latter, there may also have been differences in ergot-related history between the rams, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for generating the face stimuli was similar to that described by Derenne (2010). Each time a set of stimuli was created, a photograph of a face was taken with a Sony Cyber-Shot DSC-w1 5.1 megapixel digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…That is, in these cases it is possible to identify stimuli that function in a similar manner as S+and S-, and the organism tends to respond to relatively extreme stimuli (i.e., stimuli very different from S-). Examples include the evolution of sexual dimorphism (ten Cate et al 2006;Weary et al 1993) and aposematic coloration (Gamberale and Tullberg 1996;Gamberale-Stille and Tullberg 1999;Yachi and Higashi 1998), the preference for supernormal stimuli and caricatures (Ghirlanda andEnquist 1999, 2003;Ramachandran and Hirstein 1999;Zimmer 2003), changes in speech patterns (Martindale 2006), and extreme responses in certain forms of mental illness (Derenne 2010;Dunsmoor et al 2009Dunsmoor et al , 2011.…”
Section: Patterns Of Stimulus Generalization Vary With Experiencementioning
confidence: 99%